Natural products from microbes associated with insects - Beemelmanns, Christine; Guo, Huijuan; Rischer, Maja; Poulsen, Michael (Beilstein Journal of Organic Chemistry, 2016)
Here we review discoveries of secondary metabolites from microbes associated with insects. We mainly focus on natural products, where the ecological role has been at least partially elucidated, and/or the pharmaceutical properties evaluated, and on compounds with unique structural features. We demonstrate that the exploration of specific microbial–host interactions, in combination with multidisciplinary dereplication processes, has emerged as a successful strategy to identify novel chemical entities and to shed light on the ecology and evolution of defensive associations.
Keywords: biosynthesis; chemical ecology; natural products; secondary metabolism; structure elucidation; symbiosis